2009
DOI: 10.1093/geront/gnp024
|View full text |Cite
|
Sign up to set email alerts
|

The National Nursing Assistant Survey: Improving the Evidence Base for Policy Initiatives to Strengthen the Certified Nursing Assistant Workforce

Abstract: This survey can be used to understand CNA workforce issues and challenges and to plan for sustainable solutions to stabilize this workforce. The NNAS can be linked to other existing data sets to examine more comprehensive and complex relationships among CNA, facility, resident, and community characteristics, thereby expanding its usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 6 publications
0
80
0
1
Order By: Relevance
“…Squillace et al (2009) reported that years of CNA experience do not render higher wages, showing a disregard for the years of practical knowledge and firsthand experience. In our study, many CNAs described frustration with lack of respect for their input, despite spending more direct time with residents than other staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Squillace et al (2009) reported that years of CNA experience do not render higher wages, showing a disregard for the years of practical knowledge and firsthand experience. In our study, many CNAs described frustration with lack of respect for their input, despite spending more direct time with residents than other staff.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there is a shortage in the United States of CNAs in nursing homes, which is an issue that has serious consequences for the quality of care provided (Squillace et al 2009). Studies have demonstrated a relationship between CNA staffing levels and nursing home quality (Hyer et al 2011).…”
mentioning
confidence: 99%
“…[12,13] Nursing home staff report that aggression is the most distressing behavior in PWDs, and approximately 50% of nursing assistants report being injured because of aggressive behavior. [14,15] Caregivers who experience aggression from a PWD report higher caregiver burden, experience worse physical functioning, and have higher pain scores. [13] In turn, this can lead to staff burnout and high turnover rates, which will likely reduce the quality of care and increase the cost of care.…”
Section: Prevalence Of Aggression In Pwdsmentioning
confidence: 99%
“…[23][24][25] Also, as mentioned previously, long-term care staff report aggression during ADLs as highly distressing, and there is an increased risk of injury to both caregivers and PWDs. [14,15] In our previous review, only 6 of 18 studies specifically targeted aggression during ADLs and it was recommended that additional studies address this important issue. [29] Since that time, just four additional studies that met the inclusion criteria have been devoted specifically to addressing aggression during ADLs.…”
Section: Targets Of Interventionsmentioning
confidence: 99%
“…We did not examine eligibility for or enrollment in any of the benefits, and low participation rates may influence whether these benefits are made widely available to NA staff. For example, some NAs cannot afford to participate in their employer's health plan (Squillace et al, 2009), and high turnover rates suggest that some may not be employed long enough to earn paid time off. Future research is needed to examine the use or importance of various benefits among NAs.…”
Section: Limitationsmentioning
confidence: 99%